Erk1/2 Mediates Leptin Receptor Signaling in the Ventral Tegmental Area - Trinko, Richard (Public Library of Science, 2011)
Leptin acts on the ventral tegmental area (VTA) to modulate neuronal function and feeding behavior in rats and mice. To identify the intracellular effectors of the leptin receptor (Lepr), downstream signal transduction events were assessed for regulation by direct leptin infusion. Phosphorylated signal transducer and activator of transcription 3 (pSTAT3) and phosphorylated extracellular signal-regulated kinase-1 and -2 (pERK1/2) were increased in the VTA while phospho-AKT (pAKT) was unaffected. Pretreatment of brain slices with the mitogen-activated protein kinase kinase -1 and -2 (MEK1/2) inhibitor U0126 blocked the leptin-mediated decrease in firing frequency of VTA dopamine neurons. The anorexigenic effects of VTA-administered leptin were also blocked by pretreatment with U0126, which effectively blocked phosphorylation of ERK1/2 but not STAT3. These data demonstrate that pERK1/2 may have a critical role in mediating both the electrophysiogical and behavioral effects of leptin receptor signaling in the VTA.